Indirect Victims of Child Sexual Abuse: Preliminary findings from research on the needs of and support for families of child sexual abuse - Davies, Pamela (2014)
Child sexual abuse is a complex and highly emotive subject. This research focuses on what victimologists sometimes called ‘indirect’, tertiary’ or even ‘secondary’, ‘victims’. These people are those non-abusers who are close to the ‘primary’ or ‘direct’ victim/s – the abused child/children. Indirect victims might be parents, carers, guardians, siblings, grandparents or friends. The experiences and needs of these people have rarely been the subject of research; yet the small number of (mostly US-based) studies of families of children subjected to sexual assault point to the profound impacts such offences can have, particularly on mothers. This poster reports on some preliminary findings from my ongoing research on the needs of and support for families of child sexual abuse. Findings derive from discussions with key contacts and from semi-structured interviews with key professional staff working in agencies involved in such cases. It reports in general terms on their perceptions of the ‘ripple effect’ emanating from child sexual abuse. Specifically it reports on their perceptions of who is affected, how people are affected, what their needs are and what services/support is available. Ultimately the research examines the scope and adequacy of extant support structures with a view to minimising risk and reducing harm in families